Pengaruh Pemberian Jus Alpukat Terhadap Kadar Hemoglobin Ibu Hamil Trimester III dengan Anemia di Desa Atar Bawang Kabupaten Lampung Barat - Cindi Diana Novita; Lili Anggraini (Malahayati Nursing Journal, 2024)
ABSTRACT Pregnant women who experience anemia in Indonesia are 48.9%. As much as 84.6% of anemia in pregnant women occurs in the age group of 15-24 years. Giving avocado juice can help increase hemoglobin levels because avocados are rich in iron and copper which are beneficial for pregnant women. This study aims to determine the effect of giving avocado juice on hemoglobin levels in third trimester pregnant women with anemia in Atar Bawang Village, West Lampung Regency. Type of quantitative research and pre-experimental design with Non-Equivalent Control Group. The population of all third trimester pregnant women is 20 people. Sampling using purposive sampling technique, statistical tests used paired t test (paired t test), The results showed that the average increase in hemoglobin levels before being given avocado juice to third trimester pregnant women with anemia had an average value of 10.51 gr/dl. The average increase in hemoglobin levels after being given avocado juice to third trimester pregnant women with anemia had a value the average hemoglobin level is 11.35 gr/dl. There is an effect of giving avocado juice on hemoglobin levels in third trimester pregnant women with anemia, with a p-value = 0.000. It is recommended that pregnant women be active in seeking information and increase their knowledge so that they know more about anemia in pregnancy and are advised to carry out routine pregnancy checks and it is recommended that pregnant women consume more iron-containing foods and can actively participate in maternal classes and activities at posyandu. as well as making avocado juice as an effort to prevent anemia during pregnancy. Keywords: Avocado Juice, Hemoglobin Levels, Anemia ABSTRAK Ibu hamil yang mengalami anemia di Indonesia sebesar 48,9%. Sebanyak 84,6% anemia pada ibu hamil terjadi pada kelompok umur 15-24 tahun. Pemberian jus alpukat dapat membantu meningkatkan kadar hemoglobin karena alpukat kaya akan zat besi dan tembaga yang bermanfaat bagi ibu hamil. Penelitian ini bertujuan mengetahui pengaruh pemberian jus alpukat terhadap kadar hemoglobin ibu hamil trimester III dengan anemia di Desa Atar Bawang Kabupaten Lampung Barat. Jenis penelitian kuantitatif dan rancangan pra eksperiment dengan Non-Equivalent Control Group. Populasi seluruh ibu hamil trimester III sebanyak 20 orang. Pengambilan sampel menggunakan teknik purposive sampling, uji statistik yang digunakan uji t berpasangan (paired t test). Hasil penelitian diketahui rata-–rata peningkatan kadar hemoglobin sebelum diberikan jus alpukat pada ibu hamil trimester III dengan anemia mempunyai nilai rata-rata 10,51 gr/dl Rata–rata peningkatan kadar hemoglobin sesudah diberikan jus alpukat pada ibu hamil trimester III dengan anemia mempunyai nilai rata-rata kadar hemoglobin 11,35 gr/dl. Ada pengaruh pemberian jus alpukat terhadap kadar hemoglobin pada ibu hamil trimester III dengan anemia, dengan p-value = 0,000. Disarankan ibu hamil agar aktif dalam mencari informasi dan lebih meningkatkan pengetahuan agar lebih mengetahui tentang anemia pada kehamilan serta disarankan untuk melakukan pemeriksaan kehamilan secara rutin dan disarankan ibu hamil lebih banyak mengkonsumsi makanan yang mengandung zat besi dan untuk dapat aktif mengikuti kelas ibu serta kegiatan di posyandu. serta menjadikan jus alpukat sebagai salah satu upaya untuk pencegahan anemia dalam kehamilan. Kata Kunci: Jus Alpukat, Kadar Hemoglobin, Anemia